Intravenous itraconazole compared with liposomal amphotericin B as empirical antifungal therapy in patients with neutropaenia and persistent fever. Issue 8 (28th May 2020) - Yoshida, Isao; Saito, Akiko M.; Tanaka, Shiro; Choi, Ilseung; Hidaka, Michihiro; Miyata, Yasuhiko; Inoue, Yoshiko; Yamasaki, Satoshi; Kagoo, Toshiya; Iida, Hiroatsu; Niimi, Hiromasa; Komeno, Takuya; et al.
Summary: Background: Fungal infections are a major complication of neutropaenia following chemotherapy. Their early diagnosis is difficult, and empirical antifungal treatment is widely used, and uses of less toxic drugs that reduce breakthrough infection are required. Objective: We conducted a multicentre, open‐label, randomised, non‐inferiority trial to compare the safety and efficacy of intravenous itraconazole (ivITCZ) and liposomal amphotericin B (LAmB) as empirical antifungal therapy in patients with haematological malignancies with neutropaenia and persistent fever. Methods: Patients with haematological malignancies who developed fever refractory to broad‐spectrum antibacterial agents under neutropaenia conditions were enrolled. Patients were randomised for treatment with LAmB (3.0 mg/kg/d) or ivITCZ (induction: 400 mg/d, maintenance: 200 mg/d). Results: Observed overall favourable response rates of 17/52 (32.7%) and 18/50 (36.0%) in the LAmB and ivITCZ groups, with a model‐based estimate of a 4% difference (90% CI, −12% to 20%), did not fulfil the statistical non‐inferiority criterion. In the LAmB group, there were two cases of breakthrough infection and five cases of probable invasive fungal disease, whereas in the itraconazole group, neither breakthrough infection nor probable invasive fungal disease occurred. Patients in the ivITCZ group had significantly fewer grade 3‐4 hypokalaemia‐related events than LAmB group patients ( P < .01). The overall incidence of adverse events tended to be lower in the ivITCZ group ( P = .07). Conclusion: ivITCZ showed similar efficacy and safety as LAmB as empirical antifungal therapy in haematological malignancy patients with febrile neutropaenia, although the small sample size and various limitations prevented demonstration of its non‐inferiority.